Determination of Polycyclic Aromatic Hydrocarbons (PAHs) Using Environmentally Friendly Liquid Chromatography - Kurnia, Asep; Lim, Lee Wah; Takeuchi, Toyohide (Makara Journal of Science, 2018)
An analytical methodto determine polycyclic aromatic hydrocarbons (PAHs) is required to obtain high-quality analytical results. The purpose of this study is to achievegood separation ofa few PAHs by using environmentally friendly liquid chromatography. Accordingly, a liquid chromatograph incorporating a fluorescence detector, UV detector, and a capillary column is employed herein to simultaneously minimize the use of chemicals and obtain analytical results better than those obtained using aconventional column. Observation parameter include single analysis ofeach PAH, method valida-tion, the new stationary phase, the effectof mobile phase concentration, and Quenchereffect. The PAHs tested include naphthalene, phenanthrene, anthracene, fluoranthene, and pyrene. The test results show that when using an acetonitrile concentration of 100%, the retention times of different PAHs do not differ significantly. Furthermore, upon decreasing the acetonitrile concentration, the retention time increases, and better separation was achieved. The value ranges of precision, LOD, LOQ, and linearity are 3.43 – 12.42%, 4.7–15.1 mg/L, 15.6 – 50.5 mg/L, and 0.87–0.99, respectively. The new Sil-S-ImC30 stationary phase showed good results in terms of separation of PAHs. Likewise, the use of 60, 70, 80, and 90% acetonitrile as the mobile phase in combination with 0.03 M acrylamide as the quencher affected retention time but not separation.